2010
DOI: 10.1002/jmri.22284
|View full text |Cite
|
Sign up to set email alerts
|

Manganese transport in the rat optic nerve evaluated with spatial‐ and time‐resolved magnetic resonance imaging

Abstract: Purpose: 1) To evaluate a novel theoretical model for in vivo axonal Mn 2þ transport with MRI data from the rat optic nerve (ON); and 2) to compare predictions from the new model with previously reported experimental data. Materials and Methods:Time-resolved in vivo T 1 -weighted magnetic resonance imaging (MRI) of adult female Sprague-Dawley rat (n ¼ 9) ON was obtained at different timepoints after intravitreal MnCl 2 injection. A concentration-dependent and a rate-dependent function for the Mn 2þ retinal gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…contingent on a multitude of parameters, including rate of uptake of Mn 2þ at the injection site, density of axonal projections, and proximity to the cell body (17,21). In poikilothermic fish and frog species, this rate of uptake is significantly reduced to 1/4th-1/ 8th, depending on ambient temperature, and is estimated to be in the range of $0.25-0.50 mm/h.…”
Section: Discussionmentioning
confidence: 99%
“…contingent on a multitude of parameters, including rate of uptake of Mn 2þ at the injection site, density of axonal projections, and proximity to the cell body (17,21). In poikilothermic fish and frog species, this rate of uptake is significantly reduced to 1/4th-1/ 8th, depending on ambient temperature, and is estimated to be in the range of $0.25-0.50 mm/h.…”
Section: Discussionmentioning
confidence: 99%
“…Manganese-enhanced MRI (MEMRI) has been applied in the rodent CNS (Bearer et al, 2007; Chan et al, 2011; Olsen et al, 2010; Pautler et al, 1998; Thuen et al, 2008) to investigate ion homeostasis and axonal transport. Manganese ion (Mn 2+ ), as a calcium analogue, is taken up by neurons through voltage-gated Ca 2+ channels.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Likewise, Lewis and coworkers 27 reported that the rat trigeminal nerve may also absorb and deliver manganese from the nasal cavity to the brain. The available data suggests that manganese ions that enter nerve cells are transported along the axons in an anterograde direction and also trans-synaptically, which allows for investigation of neural pathways and interneuronal connections in the olfactory system and elsewhere.…”
Section: Scientific Evidence In Support Of Olfactorymentioning
confidence: 96%